PENGARUH PROFITABILITAS, PERENCANAAN PAJAK DAN BEBAN PAJAK TERHADAP MANAJEMEN LABA (STUDI PADA PERUSAHAAN YANG TERDAFTAR DI JII TAHUN 2017-2021) - Lia Nurina; Mardiyati Mardiyati (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2023)
This study aims to determine the effect of profitability, tax planning and tax burden on corporate earnings management. Data processing in this study uses parametric statistics, especially regression analysis using eviews software. Using secondary data. This study uses company data registered on the Jakarta Islamic Index for the period 2017-2021. The research results obtained from 30 samples show that ROA has a positive and significant influence on management profits, while tax planning and tax burden do not have a significant effect on earnings management. So companies are advised to evaluate and improve their business strategies and improve their operational efficiency, such as reducing costs, increasing productivity, and increasing the use of assets. This can help increase ROA and reduce the pressure to perform earnings management.